Analisis Tingkat Kenyamanan Parkir Di Taman Beringin Medan - Surbakti, Asri Afriliany; Rizalitaher, Alif Saum (JUITECH: Jurnal Ilmiah Fakultas Teknik Universitas Quality, 2024)
Taman Beringin is a city forest in Medan Polonia District that does not have parking space in the park. This caused visitors to park their vehicles on Teuku Cik Ditiro Street, right in front of Taman Beringin. Teuku Cik Ditiro Street is a road with a width of 12 meters that can be traversed by 4 vehicles with 2 lanes. Parking area provided for visitors in the one-line Beringin Park on Teuku Cik Ditiro Street. The effect of using parking on the side of the Teuku Cik Ditiro road caused traffic chaos to increase, plus the presence of food vendors in front of Taman Beringin which also ate Teuku Cik Ditiro street. Visitors must park their vehicles outside Beringin Park because there is no parking area inside Beringin Park. The purpose of this research is to find out the level of parking comfort in Taman Beringin. The result obtained is that there are still aspects that cause discomfort (level of pessimism) for visitors and vehicle users regarding the level of parking comfort in Beringin Park. Comfort due to the presence of food sellers (20%), parking attendant services (40%), and traffic comfort (40%) have a lack of comfort level (level of pessimism).